TANGGUNG JAWAB PIHAK KEPOLISIAN DI POLRES MOJOKERTO DALAM PENGELOLAAN BARANG BUKTI - Putra, Muchammad Ferdin Fauzi; Borman, Syahrul; Prawesthi, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the role of the police in managing evidence during the investigation process at Mojokerto Police Resort. Evidence management is a crucial aspect of criminal law enforcement, whose success is influenced by procedural accuracy, officer integrity, and an accountable storage system. Based on normative legal research methods with statutory and legal theory approaches, it was found that evidence management at Mojokerto Police Resort has largely complied with the provisions of the Criminal Procedure Code (KUHAP), Police Regulation No. 10 of 2010, and Ministry of Law and Human Rights Regulation No. 16 of 2014. However, there are still practices of evidence utilization by certain officers under the pretext of official needs, which contradict the principle of chain of custody and pose a risk of legal violations. Therefore, strengthening accountability and internal supervision is necessary to ensure the integrity of evidence. This study contributes to the development of police policy and the improvement of evidence management governance in a juridical and professional manner